Hubungan Pola Asuh dengan Masalah Psikososial pada Anak di SD Negeri Pajang 1 Surakarta - Ihnawah, Nissa Abiyya; , Dr. Erna Herawati, Sp. K. J (2017)
Backgrounds : Psychosocial problems is important problem that the parents must know because it has impact the children to be difficult to adapt in daily activity like socialization, learn difficulty, school problems, sleep and eat problems then the behavioral problems. The Prevalency of this problems are 39.8 %. Emotional distress and the crisis in the first step of their development phase can make the children have this problems. Because of this, family function are principle parts. The family is a children primary suport group to socialization and the parents are important for the children psychosocial developing stage, thats all make parenting be able to be factor that caused psychosocial problems. Objectives : This research aims to analyze the correlations between parenting and psychosocial problems on children. Methods : It is Analitical Observational studies with cross sectional approach. Based on the technique simple random sampling the sample are 54. Parents as respondent are fill the KPAA (Parenting Questionare) and PSC-17 (Pediatric Symptom Checklist-17) then the correlation analyzed by Pearson test with Statistical Product and Service Solution (SPSS) 23.00 for Windows. Results : In the study mean value from parenting score are 42.5 and 10.65 mean value from the psychosocial problems. The data distributions are normal then The correlations analyzed by Pearson test. The result are r= 0.372 dan p= 0.005 it means there is a correlations between parenting and psychosocial problems. Conclusion : There is a possitive correlation between parenting and psychosocial problems on children at Pajang 1 Elementary School of Surakarta.